Implementasi Manajemen Pendidikan Karakter Dalam Mengembangkan Minat, Sikap Dan Perilaku Positif Siswa Di Madrasah Tsanawiyah Al Ukhuwah Kelurahan Sungai Pelunggut Kecamatan Sagulung Kota Batam - Akhmad Efendi (UNISAN JURNAL, 2024)
This research investigates the implementation of character education management at Madrasah Tsanawiyah Al Ukhuwah, focusing on the development of students' interests, factors influencing implementation effectiveness, as well as challenges faced and their solutions. Through qualitative data analysis, the study identifies that the school has been actively involved in developing students' interests by integrating character values into the curriculum and extracurricular activities. However, implementation effectiveness is influenced by stakeholder involvement, integration of character values into the curriculum, support from the school and community environment, and continuous program evaluation. Challenges include resistance to change, resource limitations, evaluation difficulties, and lack of parental and community involvement. Strategic steps can be taken to overcome these challenges, including effective socialization, resource enhancement, development of holistic evaluation systems, and increased parental and community engagement. In conclusion, this research highlights the importance of coordinated and holistic efforts in developing character education at Madrasah Tsanawiyah Al Ukhuwah, with a focus on better understanding the factors influencing implementation and efforts to address challenges. Keywords: Character Education Management, Interest, Attitude, Positive Behavior